Exploring EFL Teachers' Strategies in Teaching Reading Comprehension : A Case Study at a Junior High School in Riau - Antoni, Nurman (2010)
This study is aimed at exploring EFL teachers' strategies in teaching reading comprehension at one junior high school in Riau. It was conducted to get detailed information about the strategies used by teachers in teaching reading comprehension and the students' responses toward their teachers' strategies in teaching reading comprehension. To collect the data needed, this study employed a qualitative research design which is a case study using three data collection techniques; observation, interview and questionnaire. Observation was used to get main data about teachers' strategies in teaching reading comprehension and to get the information of the students' responses toward their teacher strategies. Interviews and questionnaire were used to support the data gathered from classroom observation. All of the data were analyzed by using three major phases of analyses: data reduction, data display, and conclusion drawing and verification (Miles and Huberman: 1994). This study revealed that the teachers used teaching reading comprehension strategies in three reading stages; pre, while and post reading stages. In pre-reading stage, they used brainstorming, encourage student to use dictionary, discussing text types and predicting. Then, in while-reading stage, they conducted reading aloud, reread for checking comprehension, direct reading activity, discussing unknown words and retelling the text. In post-reading stage, they created evaluating comprehension, clarifying and justifying, scanning, reviewing, assignment and follow-up. Then in general, the students' responses to their teachers' strategies were good enough which were classified into low-level association responses and partly-formed knowledge structure responses. Based on those findings, it can be concluded that (1) the three teachers need to increase their knowledge and experience in order to understand the concepts, implementations and the reasons in using the strategies in teaching reading comprehension. (2) They are suggested to give instructions of teaching strategies to students with low-level association responses before starting the reading activities, and give some guidance to students with partly-formed knowledge. This study recommended that EFL teachers in Indonesia should have self-awareness to use these kinds of teaching reading comprehension strategies. This study also recommended the headmasters to facilitate the teachers' needs and to conduct the teaching training activities. Finally, this study recommended other researchers to investigate the teaching reading comprehension practice with the teachers who have been trained to use appropriate strategies.